Sex differences in cardiorespiratory control under hypoxia: the roles of oxygen desaturation and hypoxic exposure time - André Luiz Musmanno Branco Oliveira; Gabriel Dias Rodrigues; Gabriel Dias Rodrigues; Bruno Moreira Silva; Philippe de Azeredo Rohan; Pedro Paulo da Silva Soares (Frontiers in Cardiovascular Medicine)
IntroductionMales and females differ anatomically and functionally in cardiorespiratory regulation, with males tending to experience greater oxygen desaturation under hypoxia. Therefore, sex might moderate cardiorespiratory responses to acute hypoxia exposure. Accordingly, we hypothesized that sex differences in cardiovascular and ventilatory responses would be more pronounced with equal hypoxia duration (iso-time) but less pronounced at similar oxygen desaturation levels (iso-saturation).MethodsTwenty-two (12 females) healthy individuals were exposed to normoxia (10 min at FiO2 = 0.21) and hypoxia (10 min at FiO2 = 0.115), respectively. Pulse oxygen saturation (SpO2), R-R intervals, cardiac output, blood pressure (BP), and ventilatory data were continuously recorded during spontaneous breathing. Spectral analysis of R-R intervals and systolic BP revealed cardiovascular autonomic modulation in the low- (LF; 0.04–0.15 Hz) and high-frequency (HF; 0.15–0.40 Hz) bands and alpha-index (α–LF) assessed spontaneous baroreflex sensitivity (BRS). Sex differences were compared in iso-saturation and iso-time analyses.ResultsAt 10 min of hypoxia (iso-time), males desaturated more than females (interaction: p = 0.004), and hypoxia-induced tachycardia in both groups (p < 0.001), but no “sex-time” interaction was found for cardiovascular data. In contrast, only males responded with ventilatory responses during iso-time hypoxia, decreasing breathing frequency (interaction: p = 0.022) and increasing tidal volume (Vt) (interaction: p = 0.036). Otherwise, during iso-saturation (SpO2-matched ∼91%), heart rate and LF of R-R intervals increased more in females than in males (interaction: p = 0.049). However, only males increased Vt (interaction; p = 0.037).ConclusionOur data indicate that females counterbalance hypoxia mainly by systemic circulatory adjustments, while males use both, circulatory and ventilatory adjustments.